- COMPARISON BETWEEN FINGERPRINT PATTERNS AND TOTALRIDGE COUNT IN DIABETES MELITUS PATIENTS WITH NORMAL POPULATION IN SLEMAN - utami, handayani dwi (Jurnal Forensik dan Medikolegal Indonesia, 2023)
Background: The number of people with diabetes mellitus (DM) was increased every year in all countries. Screening tools for early, inexpensive, and non-invasive DM predictors are needed. This research was conducted to see the role of dermatoglyphics in DM. Objective: To see the difference in fingerprint patterns and Total Ridge Count (TRC) in DM patients with normal population. Methods: This cross-sectional study involved 200 subjects consisting of 100 DM patients in Sleman and 100 normal respondents at the Faculty of Medicine, UII, Yogyakarta. Fingerprints are obtained by put the finger into ink stamp then print them on paper. The fingerprint images seen by magnifying glass and the TRC was calculated manually. Results: 200 subjects showed that the most frequent pattern of fingerprints appeared ie loops. Comparison of patterns between DM patients with normal respondents ie, whorl 2.5: 1; loop 1: 1,5; arch 1: 1,25, analyzed with the Mann-Whitney test (p = 0,000). TRC in DM patients was 10,730 with an average of 107 and normal respondents were 15,253 with an average of 152 in the ten fingers. TRC was analyzed using the Mann-Whitney test (p = 0,000). Conclusion: There were significant differences in fingerprint and TRC patterns between DM patients and the normal population (p = 0,000). DM patients found more whorl patterns and fewer TRC than normal respondents.